The persuasive role of generic-you in online interactions - Minxue Niu; Emily Mower Provost; David Jurgens; Susan A. Gelman; Ethan Kross; Ariana Orvell (Scientific Reports)
Abstract Persuasion plays a crucial role in human communication. Yet, convincing someone to change their mind is often challenging. Here, we demonstrate that a subtle linguistic device, generic-you (i.e., “you” that refers to people in general, e.g., “You win some, you lose some”), is associated with successfully shifting people’s pre-existing views in a naturalistic context. Leveraging Large Language Models, we conducted a preregistered study using a large ( $$N_{trials}$$ = 204,120) online debate dataset. Every use of generic-you in an argument was associated with an up to 14% percent increase in the odds of successful persuasion. These findings underscore the need to distinguish between the specific and generic uses of “you” in large-scale linguistic analyses, an aspect that has been overlooked in the literature. The robust association between generic-you and persuasion persisted with the inclusion of various covariates, and above and beyond other pronouns (i.e., specific-you, I or we). However, these findings do not imply causality. In Supplementary Experiment 2, arguments with generic-you (vs. first-person singular pronouns, e.g., I) were rated as more persuasive by open-minded individuals. In Supplementary Experiment 3, generic-you (vs. specific-you) arguments did not differentially predict attitude change. We discuss explanations for these results, including differential mechanisms, boundary conditions, and the possibility that people intuitively draw on generic-you when expressing more persuasive ideas. Together, these findings add to a growing literature on the interpersonal implications of broadening one’s perspective via a subtle shift in language, while motivating future research on contextual and individual differences that may moderate these effects.